Pemberdayaan Masyarakat Melalui Program Daur Ulang Sampah Organik dan Anorganik Pada Dukuh Sangkeh, Srigading, Bantul, DIY - Kurniari, Akhmad; Batiarkana, Khansa; Habibah, Najwa; Putra, M. Riski Ananda; Fauziah, Kholifatul (Universitas Muhammadiyah Yogyakarta, 2025)
In alignment with the Bantul Bebas Sampah 2025 initiative and following directives from Srigading Village, Sanden, Bantul, the community service team implemented a community empowerment program focused on organic and inorganic waste recycling. This initiative aimed to enhance public awareness regarding the significance of organic waste management and its utilization as compost fertilizer. The program facilitated active community participation in both learning and practical waste processing, enabling them to transform waste into valuable resources while mitigating adverse environmental impacts. The target beneficiaries were the youth of Karang Taruna Dukuh Sangkeh, Srigading, Sanden, Bantul, Yogyakarta. The methodology employed included preliminary studies, planning, implementation involving waste management socialization and hands-on practice, and program evaluation. Beyond augmenting participant comprehension and awareness, the program successfully processed 8 kilograms of waste as a sample activity. With sustained support from the village government and continuous community engagement, this program is anticipated to operate autonomously and serve as a model for other regions in adopting superior waste management systems